Intracerebral injection of CpG oligonucleotide for patients with de novo glioblastoma—A phase II multicentric, randomised study. (March 2017) - Ursu, Renata; Carpentier, Alexandre; Metellus, Philippe; Lubrano, Vincent; Laigle-Donadey, Florence; Capelle, Laurent; Guyotat, Jacques; Langlois, Olivier; Bauchet, Luc; Desseaux, Kristell; Tibi, Annick; Chinot, Olivier; et al.
Abstract: Background: Immunostimulating oligodeoxynucleotides containing unmethylated cytosine-guanosine motifs (CpG-ODN) have shown a promising efficacy in several cancer models when injected locally. A previous phase II study of CpG-ODN in patients with recurrent glioblastoma (GBM) has suggested some activity and has shown a limited toxicity. This multicentre single-blinded randomised phase II trial was designed to study the efficacy of a local treatment by CpG-ODN in patients with de novo glioblastomas. Patients and methods: Patients with a newly diagnosed glioblastoma underwent large surgical resection and CpG-ODN was randomly administrated locally around the surgical cavity. The patients were then treated according to standard of care (SOC) with radiotherapy and temozolomide. The primary objective was 2-year survival. Secondary outcomes were progression free survival (PFS), and tolerance. Results: Eighty-one (81) patients were randomly assigned to receive CpG-ODN plus SOC (39 patients) or SOC (42 patients). The 2-year overall survival was 31% (19%; 49%) in the CpG-ODN arm and 26% (16%; 44%) in the SOC arm. The median PFS was 9 months in the CpG-ODN arm and 8.5 months in the SOC arm. The incidence of adverse events was similar in both arms; although fever and post-operative haematoma were more frequent in the CpG-ODN arm. Conclusions: Local immunotherapy with CpG-ODN injected into the surgical cavity after tumour removal and followed by SOC, although well tolerated, does not improve survival of patients with newly diagnosed GBM. Highlights: Efficacy of a local treatment by CpG-28 in patients with de novo glioblastoma (GBM) was studied. Local treatment by oligodeoxynucleotides containing unmethylated cytosine-guanosine motifs was well tolerated. We studied the impact expression of the Toll-like receptor 9 status and efficacy of CpG-28. Local therapy with CpG-28 does not improve survival of patients with de novo GBM.